The Similarities and Differences Between Glomerular vs. Non-glomerular Diagnoses on Intelligence and Executive Functions in Pediatric Chronic Kidney Disease: A Brief Report - Hooper, Stephen R.; Johnson, Rebecca J.; Lande, Marc; Matheson, Matthew; Shinnar, Shlomo; Kogon, Amy J.; Harshman, Lyndsay; Spinale, Joann; Gerson, Arlene C.; Warady, Bradley A.; Furth, Susan L. (Frontiers in Neurology, 2021)
Pediatric chronic kidney disease (CKD) appears to be a heterogeneous group of conditions, but this heterogeneity has not been explored with respect to its impact on neurocognitive functioning. This study investigated the neurocognitive functioning of those with glomerular (G) versus nonglomerular (NG) diagnoses. Data from the North American CKiD Study were employed and the current study included 1,003 children and adolescents with mild to moderate CKD. The G Group included 260 participants (median age=14.7 years) and the NG Group included 743 individuals (median age=9.0 years). Neurocognitive measures assessed IQ, inhibitory control, attention regulation, problem solving, working memory, and overall executive functioning. Data from all visits were included in the linear mixed model analyses. After adjusting for sociodemographic and CKD-related covariates, results indicated no differences between the diagnostic groups on measures of IQ, problem solving, working memory, and attention regulation. There was a trend for the G group to receive better parent ratings on their overall executive functions (p<.07), with a small effect size being present. Additionally, there was a significant G group X hypertension interaction (p<.003) for inhibitory control, indicating that those with both a G diagnosis and hypertension performed more poorly than the NG group with hypertension. These findings suggest that the separation of G vs. NG CKD produced minimal, but specific group differences were observed. Ongoing examination of the heterogeneity of pediatric CKD on neurocognition, perhaps at a different time point in disease progression or using a different model, appears warranted.